Why am I me? - Britt, Paige; Qualls, Sean; Alko, Selina (New York Scholastic Press, 2017)
In a poetic, philosophical exchange, two children of different races ask themselves why they are who and what they are, and speculate on how they could be different.
School Library Journal starred, July 2017
Pub Weekly, July 2017
Kirkus Starred, July 2017
New York Times, August 2017
Horn Book, September 2017
Bulletin (Center for Children's books), October 2017
Keywords: Identity (Philosophical concept) -- Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Identity -- Fiction; Interpersonal relations -- Fiction; Picture books